S.A.P.H.O. syndrome in childhood. Report of three cases. - Bellosta, M.; Domaneschi, E.; Rossi, S.; Caporali, R.; Montecucco, C. (European Journal of Pediatric Dermatology, 2018)
The Authors report three patients whose age ranged between 13 and 15, affected by acne nodular cystic or conglobata associated with arthropathy. These cases should be included in the so called S.A.P.H.O. syndrome. Finally they discuss the response to the treatment.